Left-Sided Pericardial Cyst Mimicking Acute Coronary Syndrome - Ezzedine, Ahmad M.; Khoury, Samih B.; Ramadan, Nagham; Bjaiji, Mohammad; Bechara, Tony; Tarhini, Fadlallah (International Journal of Innovative Research in Medical Science, 2023)
Pericardial cysts are rare clinical entities mostly asymptomatic and detected incidentally. Albeit rare, many complications are reported and extend from cough and dyspnea to sudden cardiac death. The case presented herein is the first large and localized hemorrhagic pericardial cyst mimicking an acute coronary syndrome (ACS) with intense chest pain, precordial ST-segment elevation, and elevated troponin. Following thorough investigations, this cyst appeared to be associated with moderate pericardial effusion explaining myopericarditis as a cause of the findings listed. After surgical excision, the patient experienced relief of his symptoms, and Serial electrocardiograms (ECG) post-operative were normalized.